ON THE SYSTEMATICS OF THE AMMONOID FAMILY BERRIASELLIDAE SPATH, 1922 - Sakharov A.S.; Pogodina I.A. (My University, 2003)
Three different classifications of the family Berriasellidae are revised. The phylogeny of the genera Euthymiceras Grigorieva, 1937, Gechiceras Sach., 1982, Transcaspiites Luppov, 1985, and Riasanites Spath, 1923 is reconstructed based on new information. The possible evolution of Euthymiceras and Neocosmoceras from Malbosiceras Grigorieva, 1937 is suggested.